2016
DOI: 10.1038/ng.3500
|View full text |Cite
|
Sign up to set email alerts
|

MYB-QKI rearrangements in angiocentric glioma drive tumorigenicity through a tripartite mechanism

Abstract: Angiocentric gliomas are pediatric low-grade gliomas (PLGGs) without known recurrent genetic drivers. We performed genomic analysis of new and published data from 249 PLGGs including 19 Angiocentric Gliomas. We identified MYB-QKI fusions as a specific and single candidate driver event in Angiocentric Gliomas. In vitro and in vivo functional studies show MYB-QKI rearrangements promote tumorigenesis through three mechanisms: MYB activation by truncation, enhancer translocation driving aberrant MYB-QKI expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
231
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(237 citation statements)
references
References 67 publications
6
231
0
Order By: Relevance
“…[37][38][39][40] Recent next-generation sequencing studies have identified gene rearrangements of NTRK1, 2, and 3 encoding novel oncogenic fusions in a variety of tumor types, including low-grade and highgrade astrocytoma. 6,[15][16][17] The NTRK2 fusion gene was first identified in pilocytic astrocytoma, with recent reports of additional fusions including QKI-NTRK2, NACC2-NTRK2, VCL-NTRK2, AGBL4-NTRK2, TRIM24-NTRK2, PAN3-NTRK2, AFAP1-NTRK2, SQSTM1-NTRK2, NAV1-NTRK2, and SLMAP-NTRK2. 6,[15][16][17]41,42 The mechanism of action of these fusion proteins in human gliomagenesis, progression, and drug resistance remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39][40] Recent next-generation sequencing studies have identified gene rearrangements of NTRK1, 2, and 3 encoding novel oncogenic fusions in a variety of tumor types, including low-grade and highgrade astrocytoma. 6,[15][16][17] The NTRK2 fusion gene was first identified in pilocytic astrocytoma, with recent reports of additional fusions including QKI-NTRK2, NACC2-NTRK2, VCL-NTRK2, AGBL4-NTRK2, TRIM24-NTRK2, PAN3-NTRK2, AFAP1-NTRK2, SQSTM1-NTRK2, NAV1-NTRK2, and SLMAP-NTRK2. 6,[15][16][17]41,42 The mechanism of action of these fusion proteins in human gliomagenesis, progression, and drug resistance remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…6,[15][16][17] The NTRK2 fusion gene was first identified in pilocytic astrocytoma, with recent reports of additional fusions including QKI-NTRK2, NACC2-NTRK2, VCL-NTRK2, AGBL4-NTRK2, TRIM24-NTRK2, PAN3-NTRK2, AFAP1-NTRK2, SQSTM1-NTRK2, NAV1-NTRK2, and SLMAP-NTRK2. 6,[15][16][17]41,42 The mechanism of action of these fusion proteins in human gliomagenesis, progression, and drug resistance remains poorly understood. In this study we performed a systematic screen of TK-TELs, which suggested that activated TrkB could transform Ink4a −/− /Arf −/− astrocytes in vivo via upregulation of pSTAT3 signaling and Ccl2 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QKI may also directly regulate SOX2 expression via specific binding to its mRNA 3 ′ UTR in a cis-element-dependent way . Recently, MYB-QKI fusions were identified as a specific and single candidate-driver event in angiocentric gliomas (Bandopadhayay et al 2016). In vitro and in vivo functional studies demonstrated that MYB-QKI rearrangements promote tumorigenesis through three mechanisms: MYB activation by truncation, enhancer translocation driving aberrant MYB-QKI expression, and hemizygous loss of the QKI tumor suppressor (Bandopadhayay et al 2016).…”
Section: Qki-quaking Kh Domain Containing Rna Bindingmentioning
confidence: 99%
“…37 Additionally, alterations in MYB and MYBL1, primarily fusion events, have been observed in angiocentric gliomas and low-grade astrocytomas. 30,45 Clinical trials for targeted therapy addressing some of these various abnormalities are ongoing or in development. 30,46 Given the large number of diagnostic entities with overlapping histologic and molecular features in this category, the diagnostic approach is less algorithmic than for infiltrating gliomas.…”
Section: Poorly Infiltrative Glial and Glioneuronalmentioning
confidence: 99%